Judith Hart Burling papers - Burling, Judith Hart, 1900-; Berlin, Arthur
Scrapbooks of letters, clippings, photographs, and notes relating to Burling's travels in the Orient and China, Chinese art, poetry, theater, and motion pictures. Includes letters and other papers of Arthur Berlin, Inspector General of Customs, Shanghai.
Author and orientalist.
Collection material in English.
Keywords: Art, Chinese; Chinese poetry; Motion pictures -- China; Theater -- China; China -- Description and travel; East Asia -- Description and travel; Authors; Orientalists